ON THE THERMAL RADIO EMISSION OF THE CYGNUS LOOP - POVEDA, ARCADIO (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1967)
A model of supernova remnants of Type II inspired only by the optical evidence implies a thermal radio emission which is in accord with current measurement of the flux density from the Cygnus Loop and that, therefore, its radio flux is mostly thermal at 1
BOL OBS TONAN TACUB
Keywords: THERMAL, RADIO EMISSION, CYGNUS LOOP; ASTRONOMIA Y ASTROFISICA; ASTRONOMIA OPTICA; ASTRONOMIA DE POSICION